ASYMETRIC GROWTH OF MACULAR ATROPHY ASSOCIATED WITH UNDERLYING MATURE, NONEXUDATIVE CHOROIDAL NEOVASCULARIZATION. Issue Volume 15:Issues 6(2021) (November 2021) - Monés, Jordi; Rodríguez-Bocanegra, Eduardo; Biarnés, Marc
Abstract : Background/Purpose: To describe a case study that shows a possible association between the slow growth rate of macular atrophy and the presence of underlying mature, nonexudative choroidal neovascularization. Methods: Case report. Patient: An 82-year-old woman with mixed age-related macular degeneration in both eyes was followed up for 6 years, with the last ranibizumab treatment given in the left eye more than 2 years previously. Evaluations included fluorescein angiography, spectral-domain optical coherence tomography, and optical coherence tomography angiography. Results: During follow-up, there was a peculiar growth of macular atrophy, involving mainly the superior nasal sector. No signs of exudation on fluorescein angiography or spectral-domain optical coherence tomography were apparent throughout this period. However, optical coherence tomography angiography showed a mature, nonexudative choroidal neovascularization under the foveal sparing area and surrounding all the boundaries of atrophy except in the superonasal sector. Macular atrophy growth was observed mainly in the region devoid of blood vessels. Conclusion: Growth of macular atrophy was more prominent in the region where mature, nonexudative choroidal neovascularization was absent. Nutrients provided by vessels from choroidal neovascularization may provide support to adjacent retinal pigment epithelium cells, slowing down the progression of atrophy. Abstract : Follow-up for 6 years in a patient with macular atrophy indicated an overall slow rate of progression, with faster growth in a single sector. Optical coherence tomography angiography showed a mature, nonexudative choroidal neovascularization. Growth of macular atrophy was mainly observed in the region where blood vessels were absent.